Penilaian Hasil Belajar Aspek Sikap dI SD IT Tiara Az-Zahra Kota Palangka Raya - Septiola Nur Hasanah; Muslimah; Setria Utama Rizal (Attractive : Innovative Education Journal, 2024)
This research aims to determine and describe attitude assessments at the planning, implementation and reporting stages at SD IT Tiara az-Zahra, Palangka Raya city. Descriptive qualitative research is this research. Documentation, observation and interview techniques were used in the data collection process. Data collection, data reduction, data presentation, and data withdrawal are the data analysis methods used. Source triangulation was used to validate the data. Research findings include evaluating learning objectives in relation to attitude elements at Tiara Az-Zahra IT Elementary School, Palangka Raya city at the planning stage. This includes the development of tools and indicators related to KI and KD as well as attitude assessment strategies and instruments. Directly observing student behavior and documenting it in an attitude evaluation diary are two observation methods used in attitude assessment. At the reporting stage, journal notes made by students regarding spiritual and social attitudes are analyzed and presented as attitude predicates and descriptions.